PERSEPSI PASIEN STROKE TERHADAP PELAKSANAAN BIMBINGAN ROHANI DI RUANG G2 NEUROLOGI RSUDPROF. DR. ALOEI SABOE PROVINSI GORONTALO TAHUN 2016 - Andi Nuraina Sudirman; Apris Tilome (-, 2021)
In Indonesia there is an increase, 35.8% of stroke attack elderly patients and 12.9% at a younger age. Total number of stroke survivors   in  Indonesia estimated 500,000 each  year. Whereas in the case of Gorontalo City Health Departement in 2011 amounted to 5,370 inhabitants,  in  2012  totaled  5,681  cases  of  stroke  increases  soul,  men  -  men  and  women numbered 2,035 inhabitants 3,646 inhabitants. Based on data from RSUD. Prof. Dr. Aloei saboe period in 2013 as many as 507 people. Which consisted of 213 patients with Stroke Hemoragic (SH), 294 patients with Stroke Non Hemoragic. This type of research is qualitative. The number of samples is 6 people. Data analysis was done by reading the transcripts and field notes and divide into three main themes namely theme (1) Guidance The Light To Do (2) the expected guidance Method   (3) Guidance material is expected. The results showed that stroke patients experiencing physical and functional disorders of the body and cause long-term psychological responses disorders that affect a change in this life.in this research gives an overview of stroke patients' perceptions of spiritual guidance is expected.